Cultural Diplomacy in The Era of Global Communications: The Case of Eurovision - Rosberg, Elena (Research Papers, 2025)
This article examines emerging approaches in public and cultural diplomacy, focusing on their evolution in the context of globalization, digitalization, and the growing influence of social media. The primary objective is to investigate how the Eurovision Song Contest operates as a platform for contemporary cultural diplomacy, serving as a testing ground for innovative diplomatic practices within a globalized media and geopolitical landscape. The study analyzes Eurovision as a strategic tool for conveying political messages and shaping national image, highlighting its role as an arena for geopolitical discourse and the transformative impact of social media on diplomatic strategies.
Keywords: Eurovision; Cultural diplomacy; Globalization; Digitalization; Diplomatic actors